How is autism portrayed in news media? A corpus-based, mixed-methods analysis in China - Zhou, Wanting; Guan, Wei (Frontiers in Communication, 2024)
Introduction: News media play an important role in shaping public perceptions of and attitudes toward people with autism. This study examines news reports about autism in China Daily over the past 20 years, from 2003 to 2022. Methods: This study employed both quantitative and qualitative analyses. Results: The findings reveal that news coverage on autism predominantly centers on children, with a significant shift in focus from support by family members and schools to support at the broader societal and governmental levels. Further, the overall representation of autism remains predominantly negative and rooted in prejudice. In terms of gender representation, autism is often depicted more frequently as male-oriented. However, a more diverse representation of age groups has emerged. Finally, while news media subtly convey negative attitudes toward autism, they also demonstrate a concurrent concern for the condition, reflecting a complex and nuanced attitude toward people with autism. Discussion: Our study indicates that corpus-assisted critical discourse analysis allows researchers to compare news over time, thus offering insights into changing discourses. The analysis can also reduce bias and uncover the implicit attitudes of news media toward autism by analyzing patterns of words and discourses.